Propagation Characteristics of JIY10MHz Waves on the Circuit between Tokyo and Syowa Station - Hidetoshi SUGIUCHI; Ichiro YAMAZAKI; Isao SHIRO; Noriaki KOMIYA (National Institute of Polar Research, 1979)
The field strength of the standard frequency waves (JJY) at 10 MHz, measured at Syowa Station in Antarctica, for two years from January 1974 through December 1975 was compared with the value derived from the prediction method which is based on the CCIR Interim Method. According to the diurnal variation obtained, the predicted strength shows a good agreement with the measured values when the MUF of the circuit (Tokyo-Syowa) exceeds sufficiently the operating frequency. On the other hand, the predicted strength shows a large difference from the measured value when the MUF is comparable to or below the operating frequency. This discrepancy is considered to be caused partly by the E_s propaeation mode which is not taken into account in the prediction method. The examination is made in this paper for other anomalous propaeation mode such as the off-great circle path associated with the ground side-scatter, including the deviative absorption loss. The reception rate is also investigated statistically for the purpose of establishing Tokyo-Antarctica communication circuit.